Plagiarism detection system for Armenian language - Margarov, Gevorg (2017)
In the academic context, it is very important to evaluate the uniqueness of reports, scientific papers and other documents that are everyday disseminated on the web. There are already several tools with this purpose but not for Armenian texts. In this paper, a system to analyze the similarity of Armenian documents is presented. The idea is to collect a set of documents of the same domain in order to identify keywords. Then, based on that information, the system receives two documents and compares them calculating the probability of plagiarism. For that, an approach based on several levels of analysis is implemented and some of those steps allow the user interaction choosing options or adding more information.